Inventarisasi Tumbuhan Asing Invasif di Kawasan Taman Hutan Raya Ir. H. Djuanda - Ateng Supriyatna Supriyatna; Annisa Ridha Aulia; Tri Cahyanto (IAIN Ternate, 2022)
Invasive alien plant species are plant species that occupy and dominate an area so that they become one of the threats to damage ecosystems, habitats, flora and fauna. The purpose of the study was to determine the types of invasive alien plants found in the Ir. H. Djuanda Forest Park and to find out the potential use of invasive alien plant species for the community. The research design used exploratory method combined with line transect. The results showed that there were 50 species belonging to 27 families, especially in the Compositae (13 species), Poaceae (5 species), and Acanthaceae (4 species). Based on the species composition in each block, the species found in the Utilization Block (29 species) were more diverse than the Protection Block (27 species) and Collection Block (10 species). Based on the literature review, the invasive alien plant species found in the Ir. H. Djuanda Forest Park has the potential to be developed as a animal feed, medicinal plant, processed food, and ornamental plant. Keywords: Species composition, Potential, Invasive alien plants species